2015
DOI: 10.4238/2015.december.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of agro-industrial traits in sweet sorghum

Abstract: ABSTRACT. Sweet sorghum has considerable potential for ethanol production due to its succulent stalks that contain directly fermentable sugars. Since many traits need to be considered in the selection process to breed superior cultivars for ethanol production, then correlations between the traits might be of use to help the breeder define optimal improvement strategies. The aim of this study was to investigate the association between the principal agro-industrial traits in sweet sorghum, and to evaluate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
1
23
0
2
Order By: Relevance
“…Mensuraram-se os seguintes caracteres agronômicos: produtividade de massa de matéria verde por hectare (PMV), obtida a partir do corte e pesagem das plantas, sem as panículas, da área útil da parcela a 5,0 cm da superfície do solo estimada para hectare; teor de sólidos solúveis totais (BRIX), determinado por meio de refratômetro de laboratório, com correção de temperatura automática, em graus Brix (Consecana, 2006); extração de caldo (EXT), determinado pela relação entre a massa de caldo extraído com uso do moedor de cana modelo B721 Rolos Inox, com motor à gasolina, e a massa de colmos; teor de sacarose aparente no caldo, obtido com uso do polarímetro digital de peso normal (POL) (Consecana, 2006); e toneladas de sólidos solúveis totais, em graus Brix, por hectare (TBH), que foi obtido pelo produto entre PMV, BRIX e EXT (Pedrozo et al, 2008;Lombardi et al, 2015).…”
Section: Methodsunclassified
“…Mensuraram-se os seguintes caracteres agronômicos: produtividade de massa de matéria verde por hectare (PMV), obtida a partir do corte e pesagem das plantas, sem as panículas, da área útil da parcela a 5,0 cm da superfície do solo estimada para hectare; teor de sólidos solúveis totais (BRIX), determinado por meio de refratômetro de laboratório, com correção de temperatura automática, em graus Brix (Consecana, 2006); extração de caldo (EXT), determinado pela relação entre a massa de caldo extraído com uso do moedor de cana modelo B721 Rolos Inox, com motor à gasolina, e a massa de colmos; teor de sacarose aparente no caldo, obtido com uso do polarímetro digital de peso normal (POL) (Consecana, 2006); e toneladas de sólidos solúveis totais, em graus Brix, por hectare (TBH), que foi obtido pelo produto entre PMV, BRIX e EXT (Pedrozo et al, 2008;Lombardi et al, 2015).…”
Section: Methodsunclassified
“…The genotype-by-trait biplot pointed out a high positive association between TBH and EY, indicating the possibility of adopting these traits as criteria for indirect selection to obtain more productive genotypes, in terms of alcohol productivity. The path analysis conducted by Lombardi et al (2015) corroborated this, revealing that TBH showed significant direct effect on the ethanol yield.…”
Section: Discussionmentioning
confidence: 61%
“…However, only for Brix and juice pol did these significant genotypic correlations result in direct effects (greater than the residual effect) on the TRS. Working with technological variables in sweet sorghum, Lombardi et al (2015) reported strongly positive direct effects of total Brix per hectare on ethanol production per hectare, and concluded that Brix was the variable that most contributed to ethanol production.…”
Section: Resultsmentioning
confidence: 99%
“…The technique, introduced by Wright (1921Wright ( , 1923 and described in detail by Li (1956Li ( , 1975, identifies miscorrelations between two traits that may not necessarily be related by direct cause-andeffect, because of the influence of a third trait. Path analysis has been widely used by plant breeders in a variety of crops, e.g., soybean (Peter et al, 2014), corn (Faria et al, 2015), common bean (Cabral et al, 2011), green bean (Araujo et al, 2012), cowpea (Moura et al, 2012;Santos et al, 2014), rice (Marchezan et al, 2005), wheat (Kavalco et al, 2014), cotton (Hoogerheide et al, 2007;Farias et al, 2016), sweet sorghum (Lombardi et al, 2015), and sugarcane (Saccharum officinarum) (Kang et al, 1983;Reddy and Reddy, 1986;Sukhchain and Sain, 1997;Ferreira et al, 2007;Silva et al, 2009;Souza et al, 2011;Esposito et al, 2012). However, studies of this nature are still necessary, because different population structures, environments, and management strategies should be considered.…”
Section: Introductionmentioning
confidence: 99%